Uso de actividades didácticas en el aprendizaje de la ortografía en estudiantes de quinto grado del Colegio Alejandro Echavarría, Medellín - Vélez Rúa, Bibian Yulieth (2025)
Spelling learning is a fundamental component of the development of written communicative competence in primary education; however, numerous studies report persistent spelling difficulties among students, largely associated with the predominant use of traditional and poorly motivating teaching methodologies. The objective of this study was to evaluate the influence of didactic activities on spelling learning among fifth-grade primary education students from a public educational institution in Medellín, Colombia. The study was conducted using a mixed-methods approach, with a pre-experimental one-group pretest–posttest design, within the framework of action research. The sample consisted of 25 students. Data collection instruments included an initial diagnostic test, a final test, an open-ended questionnaire, a student perception survey, and an observation checklist. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The results showed a significant improvement in students’ spelling performance, with correct responses increasing from 39% in the diagnostic test to 84% in the final test. In addition, qualitative findings revealed increased motivation, active participation, and confidence in the application of spelling rules related to homonyms, punctuation marks, capitalization, and accentuation. It is concluded that the implementation of playful and contextualized didactic activities has a positive influence on spelling learning by fostering comprehension, motivation, and active classroom engagement.